HIV Enteropathy in an Adolescent Bangladeshi Girl: A Case Report - Akter, Hazera; Tasmeen, Ruhina; Sarker, Mst Naznin; Rukunuzzaman, Md (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
We report a case of 14 years old girl who presented with intractable diarrhoea, low-grade irregular fever, multiple painful oral ulcers, recurrent boils over different parts of the body for 1 year, and weight loss for 6 months. Previously she was erroneously diagnosed as intestinal tuberculosis. The patient did not respond to antitubercular drugs. She also got prednisolone and mesalamine as the treatment of inflammatory bowel disease. Now she is diagnosed as a case of AIDS-stage 3. We describe the case and discuss its clinical and biochemical findings with treatment. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):49-52